1995
DOI: 10.21273/jashs.120.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Yield and Fruit Quality of French Prune to Water Deprivation at Different Fruit Growth Stages

Abstract: The sensitivity of French prune (Prunus domestica L. syn. `Petite d'Agen') to water deprivation at various fruit growth stages was studied over 3 years in a drip-irrigated orchard. The soil was a poorly drained Rocklin fine sandy loam with a hardpan that varied from 4.75 to I m from the surface at the northern end of the orchard (shallow soil condition) to no hardpan apparent to 2 m below the surface at the southern end of the orchard (deep soil condition). Water deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
2
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 16 publications
6
20
2
6
Order By: Relevance
“…We think this higher variability was due to water stress in vines growing in zones with shallower soils. This is similar to what Lampinen et al (1995) found when comparing different soil types under RDI. Maximum yield in 2009 was higher than those in (Table 1).…”
Section: Implications Of Vineyard Spatial Variabilitysupporting
confidence: 90%
“…We think this higher variability was due to water stress in vines growing in zones with shallower soils. This is similar to what Lampinen et al (1995) found when comparing different soil types under RDI. Maximum yield in 2009 was higher than those in (Table 1).…”
Section: Implications Of Vineyard Spatial Variabilitysupporting
confidence: 90%
“…However, even when irrigation intervals were shortened to every 3 d, almond trees irrigated by microsprays had lower water potentials during periods of peak water demand than those irrigated daily by drip (Edstrom and Schwankl, 2004). Since water potential is well correlated to production and fruit size in tree fruit (Naor, 2001;Naor et al, 1995Naor et al, , 1999, lower water potentials between irrigations may be most critical in midseason varieties that ripen during summer months, especially in trees with heavy crop loads during Stage III of fruit development (Lampinen et al, 1995, Marsal et al, 2005Naor et al, 2001). The cultivar used in the present study was an early-season variety that ripened in late May to early June.…”
Section: Discussionmentioning
confidence: 99%
“…RDI has been adopted extensively to control vegetative growth of deciduous trees (Boland et al, 1993;Caspari et al, 1994;Chalmers et al, 1986;Fereres and Goldhamer, 1990;Lampinen et al, 1995;Mitchell et al, 1989). In contrast to the significant effect of soil volume, RDI had minimal influence on tree growth in the current experiment (Tables 4, 5 and 6).…”
Section: Discussionmentioning
confidence: 99%